Business Judgment Rule from the Perspective of Director's Liability: A Comparative Study of Indonesia and the United States - Henin Dyah Syafrina (KRTHA BHAYANGKARA, 2026)
This research examines the structural weaknesses in the application of the Business Judgment Rule (BJR) within the Indonesian legal framework governing directors’ liability, particularly the absence of clear normative parameters and judicial standards for assessing good faith, due care, and informed decision-making. As a result, law enforcement practices frequently adopt a result-oriented approach that equates corporate losses with legal fault, thereby exposing directors acting in good faith to potential criminal liability. This study aims to analyze the regulatory and doctrinal gaps in the Indonesian BJR framework and to propose a more coherent legal model aligned with international corporate governance standards. The research employs normative doctrinal legal research using statutory, conceptual, and comparative approaches, supported by an analysis of judicial reasoning and case law, particularly from the United States where the BJR has evolved through Delaware jurisprudence and the codification of the Model Business Corporation Act (MBCA) 2016. The findings indicate that although elements of the BJR are implicitly recognized in Article 97 paragraph (5) of the Indonesian Company Law, the absence of explicit doctrinal structure and consistent standards of judicial review has contributed to the overcriminalization of directors’ business decisions involving ordinary commercial risks. Indonesian courts and law enforcement authorities therefore tend to emphasize outcomes rather than the integrity of the decision-making process. This research contributes by proposing a normative reconstruction of the BJR through clearer codification of its elements, integration with fiduciary duty principles, and the development of enforcement guidelines designed to distinguish legitimate business judgment from unlawful conduct, thereby strengthening legal certainty while maintaining balanced corporate accountability.